Composition of feathers and pulp of two broiler genotypes - Leme, B. B. [UNESP]; Sakomura, N. K. [UNESP]; Vargas, L. [UNESP]; Nascimento, C. C.N. [UNESP]; Antayhua, F. A.P. [UNESP]; Dorigam, J. C.; Macari, M. [UNESP]; Gous, R. M. (Taylor & Francis, 2022)
1. Cobb and Ross broilers (200 of each sex and breed) were fed four phases of diets ad libitum formulated with balanced protein to match their amino acid requirements throughout growth. Ten birds per genotype were sampled and euthanised at two-weekly intervals from 14 to 112 d of age. All feathers were dry-plucked from each of the seven tracts (specific skin areas) and pulp (the centre of the feather filament) was removed from primary and secondary remiges. 2. Daily losses of feathers were collected from an additional 20 individually-caged broilers of each breed. These feathers were separated into natal down, contour feathers, remiges and rectrices and then pooled by type, sex and genotype to quantify water and protein contents. Only those feathers collected from male Cobb 500 MX broilers were analysed for amino acid content. 3. Amino acid contents of feathers from the seven tracts were measured only in Cobb males on days 1, 28 and 70; for pulp on days 28 and 70; and for the four types of moulted feathers. 4. Protein content on a dry matter basis remained relatively constant over all ages and tracts during growth. Water content decreased with age in both sexes and genotype. Lysine and methionine content in feathers decreased with age while cystine, valine, leucine and serine increased. Lysine, methionine and histidine levels were higher in pulp than in mature feathers whereas cystine and valine were higher in mature feathers than in pulp. 5. These results, together with information about moulting patterns in broilers, enabled the effects of age of the bird and of the type of feather, to be taken into account when determining the rate of deposition of amino acids in feathers.
Keywords: Amino acids; contour feathers; feather tracts; moulting; natal down; rectrices; remiges